2009
DOI: 10.1111/j.1439-0272.1976.tb01671.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Determination of High Molecular Weight Serum Proteinase Inhibitors in Human Semen

Abstract: Human seminal plasma contains high molecular weight and low molecular weight proteinase inhibitors. High molecular weight proteinase inhibitors are acid-lable and probably originate from serum. The following serum proteinase inhibitors are wellknown: alpha1 mtitrypsin, alpha1 ,x-antichymotrypsin, inter-alpha-trypsin inhibitor, antithrombin 111, alpha2-neuramino-glycoprotein and alpha2-macroglobulin (Heimburger et al. -1971).In contrast low molecular weight proteinase inhibitors are acidstable and are specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Our finding coincided with the data, which have shown that azoospermic ejaculates had lower mean AAT concentration compared to oligo-zoospermic and normo-zoospermic ejaculates (Schill 1976). Handelsman et al (1986) found reduced semen volume in infertile men with homozygous ZZ AAT deficiency.…”
Section: Alpha-1 Antitrypsin In Klinefelter's Syndromesupporting
confidence: 95%
“…Our finding coincided with the data, which have shown that azoospermic ejaculates had lower mean AAT concentration compared to oligo-zoospermic and normo-zoospermic ejaculates (Schill 1976). Handelsman et al (1986) found reduced semen volume in infertile men with homozygous ZZ AAT deficiency.…”
Section: Alpha-1 Antitrypsin In Klinefelter's Syndromesupporting
confidence: 95%
“…The main kallikrein inhibitor in the seminal plasma is a, proteinase inhibitor which comes from the serum where its level is 20 times higher than in the seminal plasma (Schill, 1976). However, they are rapidly inhibited by low molecular weight proteinase inhibitors found in seminal fluids.…”
Section: Components Of the Kallikrein-kinin System In Male Genital Trmentioning
confidence: 99%
“…This raises the question of which kininogenase inhibitors are present in male genital tract secretions. The main kallikrein inhibitor in the seminal plasma is a, proteinase inhibitor which comes from the serum where its level is 20 times higher than in the seminal plasma (Schill, 1976). a, proteinase inhibitor is a progressive type of kallikrein inhibitor which does not lead to an immediate inactivation of tissue kallikrein in seminal plasma.…”
Section: Components Of the Kallikrein-kinin System In Male Genital Trmentioning
confidence: 99%
“…H uman seminal plasma contains several kinds of inhibitor that are secreted from the prostate gland. The existence of many proteinase inhibitors that contain trypsin-chymotrypsin inhibitor (HUSI-I) and trypsin-acrosin inhibitor (HUSI-II), cysteine proteinase inhibitors (In-A and In-B), high-molecular-weight serum proteinase inhibitors, protein C inhibitor and acrosome reaction-inhibiting glycoprotein in human seminal plasma has been reported (Schiessler et al, 1976;Schill, 1976;Minakata et al, 1986;Christensson and Lilja, 1994;Drisdel et al, 1995). However, the existence of TIMPs that contain complexes of gelatinases and TIMPs is relatively unknown in human seminal plasma.…”
mentioning
confidence: 99%